Three-generation education patterns among grandparents, parents and grandchildren: Evidence of grandparent effects from Australia - Povey, J; Mitrou, F; Zubrick, S; Hancock, K; Campbell, A (My University, 2017)
The ways in which parents invest their human capital resources in the development of their children is well established, however the transfers of resources across multiple generations is less understood, particularly in Australia. Drawing upon information from the Longitudinal Study of Australian Children relating to the educational attainment of maternal and paternal grandmothers and grandfathers, mothers and fathers, we find that the likelihood of mothers and fathers completing Year 12 is higher among those whose own parents, and their partner’s parents, had higher educational attainment. Controlling for parent educational attainment, grandchildren had higher numeracy scores at age 8–9 years if their paternal grandfather was university qualified and higher reading scores if maternal or paternal grandmothers were university qualified. We also find that achievement scores were substantially higher among children in families with concentrations of educational advantage. These results suggest that the concentration of human capital in families contributes to educational inequalities across multiple generations.
Keywords: Ageing -- Grandparents; Education and Training; Ageing; Learning, education and training; Ageing; Education and Training; Grandparents; Learning, education and training; Ageing